Studi Etnofarmakologi Tanaman Obat Demam Oleh Penyehat Tradisional Di Desa Talang Pauh Kabupaten Bengkulu Tengah - Cindy Darma Prasiska; Ikhsan; Reza Rahmawati; Suci Rahmawati; Rizqa Hasanah (Poltekkes Kemenkes Bengkulu, 2026)
Fever is a common health condition frequently managed through traditional medicine using medicinal plants based on inherited local knowledge. This study aimed to document the species of medicinal plants, plant parts used, preparation methods, and modes of administration employed by traditional healers to treat fever in Talang Pauh Village, Pondok Kelapa District, Central Bengkulu Regency. This research was a descriptive observational study with a qualitative approach. A total sampling technique was applied involving 12 traditional healers. Data were collected through in-depth interviews and direct observation, then analyzed descriptively and presented in tables and narrative form. The results identified 29 plant species utilized for fever treatment. The plant species most frequently used by traditional healers is melur (Jasminum sambac L) Leaves were the most commonly used plant part, followed by rhizomes, roots, bark, corms, and coconut water. Boiling was the predominant preparation method, and oral administration was the most common mode of use, in addition to compressing, topical application, and bathing. The dominance of leaf usage reflects considerations of availability, ease of processing, and sustainability. These findings indicate that traditional medicinal practices in Talang Pauh Village remain well preserved and hold potential for further scientific investigation to support the development of evidence-based herbal medicine rooted in local wisdom.